Prevalence of impacted third molars and its associated pathologies among population in Sanaa city – Yemen - SHUMAR, Amenah (International Arab Journal of Dentistry (IAJD), 2020)
The objective of the present study was to determine the prevalence of impacted third molars and its associated pathologies in a random sample of Yemeni population in Sana’a. This study represents retrospective orthopantomogram (OPG) analysis of 1900 patients chosen randomly from digital x-rays centers in Sana’a, Yemen. Data collected was analyzed using Statistical Package for Social Sciences (SPSS) version 25. Among 1900 OPG’s, impacted third molars were found in 741 (39%), most commonly noticed in female 467 (63.1%), mandibular jaw 325 (43.86%), mesiangular 510 (55.9%) in mandible and distoangular 316 (52.5%) in maxilla, class IB 633 (41.84%). Associated pathology was dental caries in the second or third molar 67 (9%). Pathologies mostly affects mandible 197 (91.6%); they occur in mesioangular 98 (45.6%), class I 125 (58.1%), level B 96 (44.7%) position. As a conclusion, impacted third molar is a common problem that affects nearly one third of Yemeni population.